2007
DOI: 10.1002/qj.74
|View full text |Cite
|
Sign up to set email alerts
|

Data assimilation in the FOAM operational short‐range ocean forecasting system: a description of the scheme and its impact

Abstract: ABSTRACT:A detailed description of the data assimilation scheme used in the Forecasting Ocean Assimilation Model (FOAM) operational ocean forecasting system is presented. The theoretical basis for the scheme is an improved version of the analysis correction scheme, which includes information from previously assimilated data. The scheme requires the a priori specification of error covariance information for the background model field and the observations. The way in which these error covariances have been estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
132
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(133 citation statements)
references
References 31 publications
(32 reference statements)
0
132
0
1
Order By: Relevance
“…Argo. See Martin et al (2007) for a more detailed description of FOAM. The along track altimeter SLA data is obtained from Collecte Localisation Satellites (CLS).…”
Section: Met Office Ukmentioning
confidence: 99%
“…Argo. See Martin et al (2007) for a more detailed description of FOAM. The along track altimeter SLA data is obtained from Collecte Localisation Satellites (CLS).…”
Section: Met Office Ukmentioning
confidence: 99%
“…As one of the outcomes of the GSOP intercomparison, [25] compares the variability in state estimates from multi-decadal syntheses ( [11], [28], [29], [30], [31] [32], [33], [34], [35], [36], [37]). There is a large spread in the various estimates of some quantities such as global upper ocean heat and freshwater content (Fig.…”
Section: The Current Global Synthesis Effortsmentioning
confidence: 99%
“…Another result that is common to many studies is the necessity of assimilation of altimeter data to represent mesoscale variability (e.g., [26], [33], [102]). Reference [103] has shown that four altimeters are needed in real time to get similar quality performance as two altimeters in delayed time.…”
mentioning
confidence: 99%
“…As discussed by MW10, the 1D implicit diffusion operator is closely linked to the recursive filter (Lorenc, 1992;Hayden and Purser, 1995), which has been developed extensively in meteorology for constructing correlation models in multiple dimensions (Wu et al, 2002;Purser et al, 2003aPurser et al, , 2003bLiu et al, 2007). The recursive filter has also been employed in ocean data assimilation systems (Martin et al, 2007;Dobricic and Pinardi, 2008;Liu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%